MEMBUAT FEEDS SOSIAL MEDIA INSTAGRAM SEBAGAI SALAH SATU MEDIA PROMOSI WISATA AGRO LEMBAH KECUBUNG: CREATING INSTAGRAM SOCIAL MEDIA FEEDS AS ONE OF THE MEDIA FOR WISATA AGRO LEMBAH KECUBUNG PROMOTION - Lutvia Febrin Sholekhaningtyas; Restu Ismoyo Aji (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Wisata Agro Lembah Kecubung is the first natural tourist destination in Penanggungan Village, Trawas District, Mojokerto Regency. Lembah Kecubung is taken from the name of a spring which is a resource for the surrounding community. Wisata Agro Lembah Kecubung itself has the theme "The Green Valley Bringing to Life" which applies natural freedom and a healthy environment. The Teaching Campus Competition Program (PKKM) Bina Desa Merdeka Belajar Merdeka Campus from the Universitas Pembangunan National "Veteran" Jawa Tinur, the Visual Communication Design Study Program (VCD) contributed to designing feeds and creating Instagram social media content as promotional media for the Wisata Agro Lembah Kecubung. The result of the activity is The promotional activities carried out are creating feeds that introduce and explain the concept of Amethyst Valley Agro Tourism, providing information in the form of facilities and rides for Amethyst Valley Agro Tourism, providing information on the operational time of the Amethyst Valley Resto, reels content in the form of an introduction from the tour, introducing the mascot of the Amethyst Valley Agro Tourism, location plans, information about vegetable picking, some funfact of vegetables, menus of Amethyst Valley Resto, food review reels content of Amethyst Valley Resto, reels content of fish therapy rides, scenery reels content in Amethyst Valley Agro Tour, landscape photos with models, mini reels content vlog to Amethyst Valley Agro Tour, and parody reels content in Amethyst Valley Agro Tourism.